2018
DOI: 10.1097/md.0000000000011879
|View full text |Cite|
|
Sign up to set email alerts
|

Factors influencing the contamination rates of the conjunctival swabs and organ culture media of human donor eyes

Abstract: This study assessed the influence of donor, environmental, and logistical factors on the contamination rates of the conjunctival swabs and organ culture media of human donor eyes.In total, 1008 conjunctival swabs and 418 organ culture media samples from 504 consecutive human donor eyes were analyzed. Cross-tabulation, chi-squared tests, and Fisher's exact tests were used to assess the influence of the different factors on the contamination rates of the conjunctival swabs and organ culture media.The overall con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…The mean time between death and the conjunctival swab collection was 12.4±15.0 h. In 2018, our study group showed that a prolonged time interval between death and the conjunctival swab collection was significantly associated with an increased conjunctival swab contamination risk [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean time between death and the conjunctival swab collection was 12.4±15.0 h. In 2018, our study group showed that a prolonged time interval between death and the conjunctival swab collection was significantly associated with an increased conjunctival swab contamination risk [17].…”
Section: Resultsmentioning
confidence: 99%
“…However, in total, we decontaminated the donor eyes for at least 8 min in low concentrations of povidone-iodine and transported the eyes separately in cooled sterile urine cups filled with 5 ml of gentamicin eye drops between the 2 decontaminations. Our extensive decontamination protocol, as described above, could explain why our organ culture media contamination rate of 1.0% was lower than the rates of 4.5% to 10.8% found by Li et al, who cleaned the periocular region with a 7.5% povidone-iodine solution spray and the ocular surface with a 1.25% povidone-iodine solution for 3 and 5 min, respectively [11,17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hermel et al, used an automated test detection system to investigate the optimal time for sterility testing [ 15 ]. Sterile swabs were used to inspect the donor’s upper and lower conjunctiva for microbial detection after povidone-iodine disinfection [ 16 ]. Thus, microbial sampling for corneal grafts is not standardized and remains a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…In the article, “Factors influencing the contamination rates of the conjunctival swabs and organ culture media of human donor eyes”, [ 1 ] which appears in Volume 97, Issue 38 of Medicine , the sentence “The different factors evaluated did not have an effect on the 8 organ culture media samples tested, and a positive conjunctival swab did not significantly increase the medium contamination risk” on page 4 should appear as “The different factors evaluated did not have an effect on the organ culture media samples tested, and a positive conjunctival swab did not significantly increase the medium contamination risk.”…”
mentioning
confidence: 99%